Resistance to TST/IGRA conversion in Uganda: Heritability and Genome-Wide 2 Association Study - McHenry, Michael L.; Benchek, Penelope; Malone, LaShaunda; Nsereko, Mary; Mayanja-Kizza, Harriet; Boom, W. Henry; Williams, Scott M.; Hawn, Thomas R.; Stein, Catherine M. (EBioMedicine, 2021)
Pulmonary tuberculosis (TB) is one of the most deadly pathogens on earth. However, the majority of people have resistance to active disease. Further, some individuals, termed resisters (RSTRs), do not develop traditional latent tuberculosis (LTBI). The RSTR phenotype is important for understanding pathogenesis and preventing TB. The host genetic underpinnings of RSTR are largely understudied. Methods: In a cohort of 908 Ugandan subjects with genome-wide data on single nucleotide polymorphisms, we assessed the heritability of the RSTR phenotype and other TB phenotypes using restricted maximum likelihood estimation (REML). We then used a subset of 263 RSTR and LTBI subjects with high quality phenotyping and long-term follow-up to identify DNA variants genome-wide associated with the RSTR phenotype relative to LTBI subjects in a case- control GWAS design, and annotated and enriched these variants to better understand their role in TB pathogenesis. Results: The heritability of the TB outcomes was very high, at 55% for TB vs. LTBI and 50.4% for RSTR vs. LTBI among HIV- subjects, controlling for age and sex. We identified 27 loci associated with the RSTR phenotype (P<5e-05) and our annotation and enrichment analyses suggest an important regulatory role for many of them. Interpretation: The heritability results show that the genetic contribution to variation in TB outcomes is very high and our GWAS results highlight variants that may play an important role in resistance to infection as well as TB pathogenesis as a whole.
Keywords: Resistance to tuberculosis infection; M. tuberculosis; GWAS; Phenotype definition; TB outcomes